Developing interactive interaction of dual buffering systems and conversion class systems with continuous supply of technological products - Lutsenko, Igor; Koval, Svitlana; Tytiuk, Valerii (Eastern-European Journal of Enterprise Technologies, 2021)
Many modern industrial production facilities consist of sequentially operating systems with a continuous supply of technological product. The task of stabilizing the qualitative and quantitative parameters of output products at all stages of such production is a very difficult task and often leads to additional time and money costs. Therefore, improving the efficiency of these processes is a relevant issue. A review of analogous solutions to this type of problem revealed the variability of their authors’ approaches. However, all of them are aimed at optimizing existing control trajectories, rather than creating a new, more accurate trajectory. Earlier, as part of the description of the basic principles of structural and parametric optimization of the management of production processes of this type, only the improved work of technological subsystems was reported. This paper describes the principles of control over the proposed dual buffering system and its interactive interaction with other technological subsystems. The introduction of buffering systems makes sequential technological subsystems more independent of each other. That makes it possible to increase the degree of freedom for each control subsystem and thereby improve the efficiency of finding the optimal mode of operation of the entire cybernetic system. A conceptual model of the dual buffering system was built, the stabilization of the quantitative parameter at the output of the buffering system was substantiated through the development of an adaptation mechanism, and simulation modeling of the synthesized system was carried out. The study shows that the use of buffering systems could improve the quality of energy utilization and reduce the wear of technological mechanisms by 14 % in general